Nghiên cứu phản ứng oxi hóa pha lỏng saccarozơ bằng H2O2 với xúc tác triaxetylaxetonat sắt - Huyen, Pham Thanh; Hai Ha, Dinh Thi; Tuong, Dao Van; Eichinger, Karl (Vietnam Journal of Chemistry, 2014)
D-glucarates are promising substances as chemopreventive agents against several different types of cancers, a practical synthesis of D-glucaric acid, is therefore of scientific and commercial interest. Since sucrose is in Vietnam an abundant and cheap raw material the reaction of sucrose with H2O2and iron tris(acetylacetonate) as a catalyst to D-glucaric acid was investigated and the results are presented in this paper. The iron tris(acetylacetonate) catalyst was characterized by FT-IR, UV-Vis and AAS. The products of the oxidation reactions were analyzed by HPLC.Keywords: sucrose oxidation, D-glucarate, glucaric acid, saccharic acid, Fe(acac)3catalyst.